EFFICACY OF HERBAL HEAT INDUCERS AND MINERAL SUPPLEMENTATIONS FOR INDUCING FERTILITY IN POST PARTUM ANOESTRUS DECCANI SHEEP - PATIL, A D; RAGHUWANSHI, D S; KUMBHAR, U B; MAINl, SHIV (The Indian Journal of Animal Reproduction, 2023)
The study was conducted to evaluate the efficacy of herbal heat inducer and mineral supplementation in 40 postpartum anoestrus Deccani Sheep. The experimental ewes were selected from Sheep unit, Veterinary College and Private Sheep units located around Udgir (MS). The animals were divided into four groups. Each group consisting ten sheep. Group I were administered orally with Capsule Janova@ 2 Cap. daily for three days, repeat the dose after 1 O days if no estrus is observed. Group II were treated with Exapar liquid (@20 ml daily/ sheep for 5 day)+ Tab. Mintrus (@one Tab./daily,for 20 days)+ Cap. Janova (@2 cap. for 3 days). Group Ill were administered withAV/UTU17 (@20 ml daily/ sheep for 5 day)+ Tab. Mintrus (@one Tab./dailyfor 20 days)+ Cap. Janova (@2 cap. for 3 days). Group IV was kept as untreated control. In group I, 80.00 per cent of the sheep showed oestrus within 127 .25 ± 4.26 hrs. and conception rate was 75.00 % with 1.67 services per conception. In Group II 90.00 per cent showed oestrus within 86.00 ± 4.53 hrs and conception rate was found to be 66.67 % with 1.5 services per conception. In Group 11190.00 per cent showed oestrus within 38.25 ± 8.58 hrs and conception rate was observed 88.89 % with 1.25 services per conception. In control group IV 30.00 per cent showed oestrus within 165.87 ± 6. 77 hrs and 33.33 % conceived with 1.5 services per conceptions. Induction of fertile postpartum oestrus in Deccani sheep was found to be effective with AV/UTU17 (herbal uterine cleanser) + Mintrus + Janova administration followed by post partum anoestrus could be treated successfully with Exapar + Mintrus + Janova combination therapy.